(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The Internet has become one of the important means used to transfer information via e-mail, social media, and others. It has become important to protect this information and find the best and most secure way to transfer and it to protect it from piracy attempts and common attacks on the Internet. In this paper, the encryption and steganography techniques are used to secure a transmitted through unsecure network. In this paper, we proposed a method for encryption images using second-order equations, then the encrypted image is embedded in the vide. The image is embedded according to the equations rather than embedding it sequentially in order to increase the security layer. The experimental results suggest that the approach proposed is achieves a high embedding ability. In addition, encryption and non-sequential selection of frames and locations for bit hiding increases the safety and robustness of the proposed system when compared to other methods of hiding information.